Deformation and retentive force following in vitro cyclic fatigue of cobalt-chrome and aryl ketone polymer (AKP) clasps. Issue 6 (June 2019) - Marie, Ali; Keeling, Andrew; Hyde, T. Paul; Nattress, Brian R.; Pavitt, Sue; Murphy, Ryan J.; Shary, Timothy J.; Dillon, Sean; Osnes, Cecilie; Wood, David J.
Graphical abstract: Highlights: Novel methods have successfully measured force in situ and 3D deformation of clasps. CoCr clasps distort more than aryl ketone polymer (AKP) clasps following fatiguing. CoCr clasps have a high initial removal force which decreases over time. AKP clasps have a lower but consistent removal force compared to CoCr. Abstract: Objective: To compare the retention force of individual clasps made from cobalt chromium (CoCr) or new aryl ketone polymer (AKP) material, Ultaire™ AKP, following prolonged fatigue testing along ideal and non-ideal paths of removal and to assess 3D deformation of the active and passive clasp tips. Methods: CoCr and AKP clasps were manufactured in their standard, respective processes, digitally scanned prior to testing, then cycled 15, 000 times over an e.max analogue crown in artificial saliva. Retentive load was measured in situ, as a function of cycles. Clasps were rescanned to assess deformation and along with their antagonists subjected to SEM to assess localised wear. Results: Distortion of the CoCr clasps was consistently larger than Ultaire™ AKP clasps, irrespective of removal path. CoCr clasps had significantly higher retentive forces than AKP clasps, for both removal paths. Ultaire™ AKP clasps showed a lower but relatively constant retentive force. The non-ideal path of removal affected retentive forces for both clasp materials. SEM showed localised removal of glaze for e.max crowns used with CoCr clasps. Significance: Ultaire™ AKP clasps showed significantly less permanent deformation and lower retentive force than CoCr clasps. Unlike CoCr, the Ultaire™ AKP clasps did not work harden, nor had as large a reduction in retentive force and accompanying permanent deformation; the retentive force for the Ultaire™ AKP clasps was consistent over 15, 000 cycles of fatigue mimicking prolonged clinical use. The AKP material was more robust; showing minimal deformation even in non-ideal paths of removal, as many patients would routinely use.